Early Recognition of Type 2 Diabetes Complications and Use of SGLT2i in Multidisciplinary Approach: Indonesian Perspective - An Expert Opinion - Aida Lydia; Ketut Suastika; Pranawa Martosuwignjo; Roy Panusunan Sibarani; Sally Aman Nasution; Soebagijo Adi Sulistijo (Acta Medica Indonesiana, 2023)
Indonesia ranks seventh with the highest number of cases of type 2 diabetes mellitus (T2DM). T2DM is associated with major undesirable complications including cardiovascular disease and chronic kidney disease. Kidneys play a major role in maintaining glucose homeostasis, leading the development of sodium glucose transporter inhibitors (SGLT2i). These inhibitors block renal sodium and glucose reabsorption. Several cardiovascular trials proved that SGLT2i have cardioprotective and renoprotective roles and have been suggested  as a drug of choice in primary and secondary prevention and management of cardiorenal complications associated with T2DM. This review highlights the need for a multidisciplinary recommendation for T2DM management in Indonesian population. Additionally, it is vital to provide the perspective of Indonesian medical experts in terms of screening, diagnosis and treatment as the outcome differs geographically. An expert panel of 6 members from Indonesia was convened to review the existing literature and develop an expert-based review/ summary on this topic. Members were chosen for their proficiency in diabetes, kidney disease and cardiovascular disease. The experts opined that the early use of SGLT2i will be effective in preventing and minimising the progression of cardiorenal complications. Moreover, a consistent multidimensional approach is necessary for improved outcomes.